Outcomes in the management of high-risk gestational trophoblastic neoplasia in trophoblastic disease centers in South America - Maestá, Izildinha [UNESP]; De Freitas Segalla Moreira, Marjory [UNESP]; Rezende-Filho, Jorge; Bianconi, Maria Inés; Jankilevich, Gustavo; Otero, Silvina; Correa Ramirez, Luz Angela [UNESP]; Sun, Sue Yazaki; Elias, Kevin; Horowitz, Neil; Braga, Antonio; Berkowitz, Ross (Elsevier, 2020)
Background South America has a higher incidence of gestational trophoblastic disease than North America or Europe, but whether this impacts chemotherapy outcomes is unclear. The purpose of this study was to evaluate outcomes among women with high-risk gestational trophoblastic neoplasia (GTN) treated at trophoblastic disease centers in developing South American countries. Methods This retrospective cohort study included patients with high-risk GTN treated in three trophoblastic disease centers in South America (Botucatu and Rio de Janeiro, Brazil, and Buenos Aires, Argentina) from January 1990 to December 2014. Data evaluated included demographics, clinical presentation, FIGO stage, WHO prognostic risk score, and treatment-related information. The primary treatment outcome was complete sustained remission by 18 months following completion of therapy or death. Results Among 1264 patients with GTN, 191 (15.1%) patients had high-risk GTN and 147 were eligible for the study. Complete sustained remission was ultimately achieved in 87.1% of cases overall, including 68.4% of ultra high-risk GTN (score ≥12). Early death (within 4 weeks of initiating therapy) was significantly associated with ultra high-risk GTN, occurring in 13.8% of these patients (p=0.003). By Cox's proportional hazards regression, factors most strongly related to death were non-molar antecedent pregnancy (RR 4.35, 95% CI 1.71 to 11.05), presence of liver, brain, or kidney metastases (RR 4.99, 95% CI 1.96 to 12.71), FIGO stage (RR 3.14, 95% CI 1.52 to 6.53), and an ultra-high-risk prognostic risk score (RR 7.86, 95% CI 2.99 to 20.71). Median follow-up after completion of chemotherapy was 4 years. Among patients followed to that timepoint, the probability of survival was 90% for patients with high-risk GTN (score 7-11) and 60% for patients with ultra-high-risk GTN (score ≥12). Conclusion Trophoblastic disease centers in developing South American countries have achieved high remission rates in high-risk GTN, but early deaths remain an important problem, particularly in ultra-high-risk GTN.
Keywords: gestational trophoblastic disease; trophoblastic neoplasms